ANALYSIS OF THE GLOBAL MUSLIM TRAVEL INDEX (GMTI) MUSLIM-FRIENDLY TOURISM IN IMPROVING COMMUNITY ECONOMY REVIEWED FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Pranika, Ranita; Ghofur, Ruslan Abdul; Madnasir, Madnasir; Zaelani, Abdul Qodir; Fasa, Muhammad Iqbal (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The Muslim-friendly tourism trend is a new phenomenon in the tourism industry. The Muslim community's demands for a tourist destination are not only limited to the uniqueness and tourist attraction of the place but also comfort and guarantees in carrying out worship. This research aims to analyze the Global Muslim Travel Index for Muslim-Friendly Tourism in Improving the Community's Economy from an Islamic economic perspective. This type of research is qualitative. This research was conducted in Lampung Province in September 2023. This data collection technique used observation and interviews. The research results show that tourism development opportunities that accommodate Muslim needs, in accordance with GMTI, act as a generator of employment opportunities to improve the economic welfare of the community. A tourist destination that is friendly to Muslim tourists is a place that offers natural beauty, comfort, cleanliness, and freshness. This area is also equipped with comprehensive facilities, ranging from places of worship to accommodation, and functions as an attractive culinary center. This tourism acts as an economic center for residents. The development of tourism potential based on Sharia principles also has a significant positive impact on surrounding communities, such as food and beverage businesses, children's toy rental service providers, and various other sectors.